(3GdUhGQe GdeGVjI aj JMbjb GdaQbI GdfGLjI hQO GdaQbI GdgGhjIs - (3GdMSjfi, GdbRhjfj, eMeO egOj Hf MSf Hf CMeO, J(B1300(3g`s ((3MSf GdehShj GdbRhjfjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj gOi hde jJQc GdNdb SOi,(B...(3hHYO ajbhd (B...(3Efg deG JTYHJ GdePGgH hGdBQGA aj HjGf GdTQjYI GdZQGA(B...s
(3BNQgG (B:s
(3aGdhGLH Ydi LejY GdCeI ELeGYG ef fUhU GdaQjbjf GdJeSc HePgHg hePgH Cgd HjJg(B...(3gPG BNQ eG ChQOg GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B114s
(3GdPQjYI(B:(3L(B15(3,U(B68(3,Qbe(B617s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds